The Arctic Ocean between Greenland and Nova Zemla and between the 60th and 82d parallel of latitude from Swedish, Danish, British, Russian and German surveys and explorations up to 1871 - Welcker, A (Washington D.C., 1882)
Kartta kuuluu A. E. Nordenskiöldin kokoelmaan Corrected July 1882 Liimattu kankaalle